Preparation method and application of NiFe2O4 / ZIF-8 catalyst based on space-time gradient assembly

Through the spatiotemporal gradient assembly method, NiFe2O4 nanoparticles are uniformly dispersed in ZIF-8, and a high-performance NiFe2O4/ZIF-8 catalyst was prepared, which solved the problem of insufficient catalyst activity of zinc-air battery and significantly improved the electrochemical performance and cycling stability. .

CN119252944APending Publication Date: 2025-01-03HENAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411470840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The kinetics of oxygen reduction reaction and oxygen precipitation reaction of zinc-air batteries are relatively slow, which limits its energy efficiency and cycling stability. The uneven distribution of existing catalysts in nanoparticles leads to insufficient catalytic activity.

Method used

NiFe2O4 nanoparticles were assembled in situ in ZIF-8 by spatiotemporal gradient assembly method. By regulating the temperature of the reaction environment and using multifunctional inducers, the uniform dispersion of nanoparticles in ZIF-8 is achieved, and high-performance NiFe2O4/ZIF-8 is synthesized. Dual-functional catalyst.

Benefits of technology

The catalytic activity and cyclic stability of the catalyst are improved, the electrochemical performance and cyclic stability of the zinc air battery are significantly improved, and the catalytic activity of oxygen reduction and oxygen precipitation is shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252944A_ABST
    Figure CN119252944A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a NiFe2O4 / ZIF-8 catalyst based on spatio-temporal gradient assembly.The preparation method comprises the steps that NiFe2O4 nanoparticles are evenly distributed in ZIF-8 growth through a spatio-temporal gradient assemblystrategy in combination with the dynamic response characteristic of an inducer to temperature and a synchronous regulation and control technology, and a NiFe2O4 / ZIF-8 precursor is formed; and transferring the precursor into a quartz boat, and carrying out pyrolysis in a tubular furnace under the protection of nitrogen, hydrogen and helium mixed gas to finally obtain the uniformly distributed NiFe2O4 / ZIF-8 catalyst. The NiFe2O4 / ZIF-8 catalyst prepared by the method can replace a noble metal catalyst which is high in cost and scarce in resource, and has a wide application prospect in the fields of energy storage and conversion such as electro-catalytic oxygen reduction reaction and zinc-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rechargeable zinc-air battery catalysts, and specifically relates to a preparation method and application of a NiFe2O4 / ZIF-8 catalyst assembled based on time-space gradients. Background Art

[0002] Zinc-air batteries (ZABs) have attracted much attention as an environmentally friendly, low-cost and high-energy-density energy system. However, the reaction kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the air cathode are relatively slow, which limits its energy efficiency and cycling stability. Therefore, these reactions require efficient catalysts to accelerate the reaction rate. Compared with precious metal-based catalysts, transition metal electrocatalysts (such as iron, cobalt, nickel, etc.) show good performance in catalyzing ORR and OER and are inexpensive. Researchers are committed to optimizing the structure and properties of these catalysts to improve the overall energy efficiency and cycling stability of the battery. Current research directions include developing new transition metal catalysts, improving the stability of catalysts, and exploring the performance of composite catalysts (such as MOF-based catalysts) in practical applications. These efforts aim to address the limitations of existing catalysts and promote the further development of Zn-air battery technology.

[0003] MOF (Metal-Organic Framework) materials are porous materials with highly ordered and adjustable structures. They are crystals formed by metal ions or metal clusters and organic ligands through coordination bonds, and have shown broad application prospects in many fields. MOF materials not only have rich pore structures, which can provide a large amount of surface area for molecular adsorption and catalytic reactions, but also the specific surface area of ​​MOF materials is usually very high, which increases the contact area of ​​catalytic reactions and greatly improves the catalytic efficiency. In addition, by selecting different metal ions and organic ligands, the pore size, structure and function of MOF can be precisely adjusted. This adjustability allows MOF materials to be optimized for specific applications. However, when using nanoparticle-composite MOF-based catalysts, there are also some challenges in regulating the distribution of nanoparticles, such as uneven distribution of nanoparticles resulting in insufficient catalytic activity. During the synthesis of MOF-based catalysts, nanoparticles may aggregate or agglomerate, which will lead to uneven distribution of active sites on the catalyst surface, thereby affecting the efficiency and selectivity of the catalytic reaction, thereby reducing the catalytic performance. Based on this, the present invention provides a method for preparing a catalyst based on spatiotemporal gradient controlled assembly, wherein the catalyst is prepared by in-situ assembly of NiFe2O4 nanoparticles in MOF material ZIF-8, and then synthesizing a high-performance NiFe2O4 / ZIF-8 bifunctional catalyst by pyrolysis, and the catalyst is used to show good catalytic activity and cycle stability in catalytic oxygen reduction and oxygen evolution reactions. At the same time, research in related fields may continue to explore how to further improve the energy performance and cycle stability of the catalyst while reducing production costs, which points the way for the application of non-precious metal catalysts in zinc-air batteries. There are currently no relevant reports in this regard. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a preparation method of a NiFe2O4 / ZIF-8 catalyst based on time-space gradient assembly. The NiFe2O4 / ZIF-8 catalyst prepared by the method is used to catalyze the ORR and OER reactions of a rechargeable zinc-air battery, thereby effectively improving the electrochemical performance and cycle stability of the rechargeable zinc-air battery.

[0005] The present invention adopts the following technical scheme to solve the above technical problems, namely, a method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly, wherein the specific process is as follows: firstly, NiFe2O4 nanoparticles are synthesized, and then, the ZIF-8 generation process is regulated under the spatiotemporal gradient, namely, the temperature of the reaction environment is precisely regulated and the hydrophilicity of the multifunctional inducer is utilized, thereby improving the dispersibility and uniformity of the NiFe2O4 nanoparticles in the ZIF-8 generation process, effectively avoiding particle aggregation, achieving uniform coating of the NiFe2O4 nanoparticles, and finally successfully realizing the synthesis of the NiFe2O4 / ZIF-8 bifunctional catalyst. The uniform dispersion of the NiFe2O4 nanoparticles in the ZIF-8 makes the prepared NiFe2O4 / ZIF-8 catalyst have ultra-high performance, including excellent catalytic activity, stability and mass transfer efficiency, thereby effectively improving the electrocatalytic activity and stability of the NiFe2O4 / ZIF-8 electrocatalytic material in practical applications. The high-performance NiFe2O4 / ZIF-8 bifunctional electrocatalyst prepared by the present invention exhibits excellent oxygen reduction and oxygen evolution catalytic activities and exhibits excellent practicality in zinc-air batteries.

[0006] The method for preparing the NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly of the present invention is characterized in that the specific steps are: Step S1, adding ferric acetylacetonate, nickel acetylacetonate and 1,2-hexadecanediol into a reaction container, then adding oleylamine oleic acid and dibenzene ether and mixing them evenly, heating to react under an inert gas environment, and after the reaction is completed, centrifuging and washing the product, and then freeze-drying it to obtain NiFe2O4 nanoparticles; Step S2: Add the NiFe2O4 nanoparticles and Zn(NO3)2·6H2O obtained in step S1 into a reaction container, then add the copolymer PNIPAM-PAA and dilute with deionized water to obtain a mixed solution A, dissolve different masses of 2-methylimidazole in methanol to obtain solutions B1 and B2, wherein the concentration of solution B1 is greater than that of solution B2; Step S3: placing the mixed solution A obtained in step S2 in a constant temperature reactor and setting the temperature to change in stages, the whole change process includes a heating stage, a constant temperature stage and a cooling stage, while the temperature of the mixed solution A changes in stages, adding solution B1 and solution B2 to the mixed solution A in stages to react, collecting the product by centrifugation after the reaction is completed, vacuum drying the product and grinding it to obtain a NiFe2O4 / ZIF-8 precursor; Step S4: The NiFe2O4 / ZIF-8 precursor obtained in step S3 is pyrolyzed at 900-1000° C. under the protection of a nitrogen, hydrogen and helium mixed gas to obtain a NiFe2O4 / ZIF-8 electrocatalyst.

[0007] It is further defined that in step S1, the feed ratio of ferric acetylacetonate, nickel acetylacetonate, 1,2-hexadecanediol, oleylamine, oleic acid and dibenzene ether is 2mmol:1mmol:6~10mmol:4~8mmol:4~8mmol:20~60mL.

[0008] It is further defined that the reaction conditions of the heating reaction process in step S1 are an oxygen-free N2 environment, and the heating reaction process is a programmed temperature increase, specifically first heating to 100-120°C and maintaining for 1-2 hours, then heating to 200-220°C and maintaining for 1-3 hours, and then continuing to heat to 290-300°C and maintaining for 1-2 hours.

[0009] It is further defined that in step S1, the centrifugation conditions are 9000-10000 rpm, the centrifugation time is 3-10 min, the washing conditions are n-hexane dispersion followed by ethanol precipitation, and the freeze-drying time is 24-60 h; in step S3, the centrifugation conditions are 8000-9000 rpm, the centrifugation time is 3-8 min, the washing solvent is ethanol, the vacuum drying temperature is 50-70°C, and the vacuum drying time is 10-15 h.

[0010] It is further defined that in step S2, the feed mass ratio of Zn(NO3)2·6H2O, NiFe2O4 nanoparticles and copolymer PNIPAM-PAA is 300~400:1:1~3; the feed mass ratio of Zn(NO3)2·6H2O and dimethylimidazole is 1:0.5~2; and the concentration ratio of solution B1 and solution B2 is 2:1.

[0011] It is further defined that the specific process of the heating stage in step S3 is heating from 30°C to 70°C, and the heating time is 30 minutes; the specific process of the constant temperature stage is maintaining at 70°C for 30 minutes; the specific process of the cooling stage is cooling from 70°C to 30°C, and the cooling time is 30 minutes.

[0012] It is further defined that in step S3, solution B1 is added dropwise to the mixed solution A during the heating stage, and the duration of adding solution B1 is consistent with the duration of the heating stage; solution B2 is added dropwise to the mixed solution A during the constant temperature stage, and the duration of adding solution B2 is consistent with the duration of the constant temperature stage.

[0013] It is further defined that the specific process of pyrolysis in step S4 is to heat the temperature to 950°C at a heating rate of 5°C / min and maintain it for 2 hours under the protection of a nitrogen, hydrogen and helium mixed gas, wherein the volume fraction of hydrogen in the nitrogen, hydrogen and helium mixed gas is 10%, the volume fraction of helium is 1%~2%, and the remainder is nitrogen.

[0014] The NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly of the present invention is used in catalyzing oxygen reduction and oxygen evolution reactions. The ORR performance of the NiFe2O4 / ZIF-8 catalyst in 0.1M KOH solution is shown as a half-wave potential of 0.88V, and the OER performance in 1M KOH solution is shown as a half-wave potential of 10mA cm -2 The overpotential is 330mV.

[0015] The invention discloses an application of the NiFe2O4 / ZIF-8 catalyst assembled based on time-space gradient in the preparation of a zinc-air battery cathode.

[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention uses a temperature-responsive copolymer PNIPAM-PAA, and achieves spontaneous regulation of the hydrophilicity and hydrophobicity of the additive under temperature changes by regulating the staged changes in temperature during the reaction process, thereby achieving the dispersion and uniformity of the nanoparticles during the growth of ZIF-8 and avoiding the instability of the reaction environment.

[0017] 2. The present invention uses an automatic titration device to accurately control the stage-by-stage change of the concentration of the 2-methylimidazole ligand during the reaction process, thereby controlling the slowness and uniformity of the ZIF-8 growth process, thereby promoting the uniform distribution of nanoparticles in ZIF-8.

[0018] 3. The present invention realizes dynamic regulation of nanoparticles by designing a multifunctional inducer and combining temperature responsiveness. The copolymer PNIPAM-PAA exhibits different hydrophilicity and hydrophobicity at different temperatures. By regulating the reaction environment, the nanoparticles present the best dispersion state at different stages. The inducer in the initial reaction system is hydrophilic, which promotes the rapid and uniform dispersion of the nanoparticles in the solvent system and the combination with the generated ZIF-8; as the temperature rises, the inducer in the reaction solution system is hydrophobic, which can better disperse the nanoparticles in the solution system and avoid agglomeration. This is of great significance for the preparation of composite materials with high dispersibility and good catalytic performance.

[0019] 4. The present invention achieves the optimal distribution and structural stability of nanoparticles in the ZIF-8 framework through multi-dimensional comprehensive regulation and protection measures. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the X-ray powder diffraction pattern of the NiFe2O4 nanoparticles obtained in Example 1.

[0021] Figure 2 This is a scanning electron microscope image of the NiFe2O4 / ZIF-8 precursor obtained in Example 1.

[0022] Figure 3 The linear voltammetric scanning curves of the NiFe2O4 / ZIF-8 catalyst obtained in Example 1 and the catalysts obtained in Comparative Examples 1, 3, and 4 in 0.1M KOH solution.

[0023] Figure 4 The linear voltammetric scanning curves of the NiFe2O4 / ZIF-8 catalyst obtained in Example 1 and the catalysts obtained in Comparative Examples 2, 3, and 4 in 1M KOH solution. DETAILED DESCRIPTION

[0024] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0025] Step S1: Accurately weigh 2mmol of ferric acetylacetonate, 1mmol of nickel acetylacetonate and 8mmol of 1,2-hexadecanediol, then add 6mmol oleylamine and 6mmol oleic acid and measure 30mL of dibenzene with a pipette. After adding a magnet, place the three-necked flask in a temperature-controllable magnetic stirrer. In a N2 atmosphere, heat it to 110℃ at a heating rate of 8℃ / min and keep it for 60min, then heat it to 210℃ at a heating rate of 3℃ / min and keep it for 2h, continue to heat it to 295℃ at a heating rate of 3℃ / min and keep it for 1h, then cool it naturally to room temperature, transfer the product to a centrifuge tube containing 20mL of ethanol, centrifuge it at 8000rpm for 8min, add 15mL of n-hexane to the precipitate obtained after centrifugation for ultrasonic dispersion, then add 20mL of ethanol to precipitate the product, and then centrifuge it at 9000rpm for 5min. After centrifugation, freeze-dry the product for 48h to obtain NiFe2O4 nanoparticles with a particle size of 10~20nm.

[0026] Step S2: Weigh 50 mg of NiFe2O4 nanoparticles and add them to a beaker containing 16.95 g of Zn(NO3)2·6H2O, then add 100 mg of copolymer PNIPAM-PAA and 300 mL of deionized water for ultrasonic dispersion to obtain a mixed solution A; add 13.2 g of 2-methylimidazole and 6.6 g of 2-methylimidazole to 150 mL of methanol, respectively, and perform ultrasonic dispersion to obtain solutions B1 and B2.

[0027] Step S3: placing the mixed solution A in a constant temperature reactor, and adding solution B1 and solution B2 to the mixed solution A using an automatic titrator while subjecting the mixed solution A to a stepwise temperature change. In the heating stage (from 30°C to 70°C, the heating duration is 30 min), the solution B1 is added using an automatic titrator. In the constant temperature stage (maintained at 70°C, the duration is 30 min), the solution B2 is added using an automatic titrator. After cooling in the cooling stage (from 70°C to 30°C, the cooling duration is 30 min), the product is centrifuged at 8000 rpm for 3 min, and then washed with ethanol 3 times. The washed product is dried in a vacuum drying oven at 60°C for 12 h, and then ground to obtain a NiFe2O4 / ZIF-8 precursor.

[0028] Step S4: The NiFe2O4 / ZIF-8 precursor was transferred to a quartz boat and placed in a tubular furnace, and a nitrogen-hydrogen-helium mixed gas (hydrogen 10 Vol%, helium 1 Vol%, and the balance nitrogen) was introduced as a protective gas, and then the temperature was increased to 950°C at a heating rate of 5°C / min and maintained for 2h, and then naturally cooled to obtain a NiFe2O4 / ZIF-8 catalyst.

[0029] Comparative Example 1 This comparative example uses 20 wt % commercial Pt / C as a control.

[0030] Comparative Example 2 This comparative example uses commercial Ir / C as a control.

[0031] Comparative Example 3 (without adding copolymer PNIPAM-PAA) Step S1: Accurately weigh 2mmol of ferric acetylacetonate, 1mmol of nickel acetylacetonate and 8mmol of 1,2-hexadecanediol, then add 6mmol oleylamine and 6mmol oleic acid and measure 30mL of dibenzene with a pipette. After adding a magnet, place the three-necked flask in a temperature-controllable magnetic stirrer. In a N2 atmosphere, heat it to 110℃ at a heating rate of 8℃ / min and keep it for 60min, then heat it to 210℃ at a heating rate of 3℃ / min and keep it for 2h, continue to heat it to 295℃ at a heating rate of 3℃ / min and keep it for 1h, then cool it naturally to room temperature, transfer the product to a centrifuge tube containing 20mL of ethanol, centrifuge it at 8000rpm for 8min, add 15mL of n-hexane to the precipitate obtained after centrifugation for ultrasonic dispersion, then add 20mL of ethanol to precipitate the product, and then centrifuge it at 9000rpm for 5min. After centrifugation, freeze-dry the product for 48h to obtain NiFe2O4 nanoparticles with a particle size of 10~20nm.

[0032] Step S2: Weigh 50 mg of NiFe2O4 nanoparticles and add them to a beaker containing 16.95 g of Zn(NO3)2·6H2O, then add 300 mL of deionized water for ultrasonic dispersion to obtain a mixed solution A after dispersion; add 13.2 g of 2-methylimidazole and 6.6 g of 2-methylimidazole into 150 mL of methanol, respectively, and perform ultrasonic dispersion to obtain solutions B1 and B2.

[0033] Step S3: placing the mixed solution A in a constant temperature reactor, and adding solution B1 and solution B2 to the mixed solution A using an automatic titrator while subjecting the mixed solution A to a stepwise temperature change. In the heating stage (from 30°C to 70°C, the heating duration is 30 min), the solution B1 is added using an automatic titrator. In the constant temperature stage (maintained at 70°C, the duration is 30 min), the solution B2 is added using an automatic titrator. After cooling in the cooling stage (from 70°C to 30°C, the cooling duration is 30 min), the product is centrifuged at 8000 rpm for 3 min, and then washed with ethanol 3 times. The washed product is dried in a vacuum drying oven at 60°C for 12 h, and then ground to obtain a NiFe2O4 / ZIF-8 precursor.

[0034] Step S4: The NiFe2O4 / ZIF-8 precursor was transferred to a quartz boat and placed in a tubular furnace, and a nitrogen-hydrogen-helium mixed gas (hydrogen 10 Vol%, helium 1 Vol%, and the balance nitrogen) was introduced as a protective gas, and then the temperature was increased to 950°C at a heating rate of 5°C / min and maintained for 2h, and then naturally cooled to obtain a NiFe2O4 / ZIF-8 catalyst.

[0035] Comparative Example 4 (without using automatic titration device for staged addition) Step S1: Accurately weigh 2mmol of ferric acetylacetonate, 1mmol of nickel acetylacetonate and 8mmol of 1,2-hexadecanediol, then add 6mmol oleylamine and 6mmol oleic acid and measure 30mL of dibenzene with a pipette. After adding a magnet, place the three-necked flask in a temperature-controllable magnetic stirrer. In a N2 atmosphere, heat it to 110℃ at a heating rate of 8℃ / min and keep it for 60min, then heat it to 210℃ at a heating rate of 3℃ / min and keep it for 2h, continue to heat it to 295℃ at a heating rate of 3℃ / min and keep it for 1h, then cool it naturally to room temperature, transfer the product to a centrifuge tube containing 20mL of ethanol, centrifuge it at 8000rpm for 8min, add 15mL of n-hexane to the precipitate obtained after centrifugation for ultrasonic dispersion, then add 20mL of ethanol to precipitate the product, and then centrifuge it at 9000rpm for 5min. After centrifugation, freeze-dry the product for 48h to obtain NiFe2O4 nanoparticles with a particle size of 10~20nm.

[0036] Step S2: Weigh 50 mg of NiFe2O4 nanoparticles and add them to a beaker containing 16.95 g of Zn(NO3)2·6H2O, then add 100 mg of copolymer PNIPAM-PAA and 300 mL of deionized water for ultrasonic dispersion to obtain a mixed solution A; add 19.8 g of 2-methylimidazole to 150 mL of methanol and perform ultrasonic dispersion to obtain a solution B.

[0037] Step S3: Pour solution B into mixed solution A and heat to 70°C for 60 minutes. After the reaction is cooled, the product is centrifuged at 8000 rpm for 3 minutes, and then washed with ethanol three times. The washed product is dried in a vacuum drying oven at 60°C for 12 hours, and then ground to obtain a NiFe2O4 / ZIF-8 precursor.

[0038] Step S4: The NiFe2O4 / ZIF-8 precursor was transferred to a quartz boat and placed in a tubular furnace, and a nitrogen-hydrogen-helium mixed gas (hydrogen 10 Vol%, helium 1 Vol%, and the balance nitrogen) was introduced as a protective gas, and then the temperature was increased to 950°C at a heating rate of 5°C / min and maintained for 2h, and then naturally cooled to obtain a NiFe2O4 / ZIF-8 catalyst.

[0039] The rechargeable zinc-air battery bifunctional catalyst prepared by the present invention has good ORR and OER bifunctional catalytic activity. Figure 3 and Figure 4 It can be seen from the electrical performance test results that the NiFe2O4 / ZIF-8 catalyst prepared in Example 1 has a larger limiting current density and half-wave potential, and the NiFe2O4 / ZIF-8 catalyst prepared in Example 1 has the best bifunctional catalytic activity.

[0040] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly, characterized in that The specific steps are: Step S1, adding ferric acetylacetonate, nickel acetylacetonate and 1,2-hexadecanediol into a reaction container, then adding oleylamine oleic acid and dibenzene ether and mixing them evenly, heating to react under an inert gas environment, and after the reaction is completed, centrifuging and washing the product, and then freeze-drying it to obtain NiFe2O4 nanoparticles; Step S2: Add the NiFe2O4 nanoparticles and Zn(NO3)2·6H2O obtained in step S1 into a reaction container, then add the copolymer PNIPAM-PAA and dilute with deionized water to obtain a mixed solution A, dissolve different masses of 2-methylimidazole in methanol to obtain solutions B1 and B2, wherein the concentration of solution B1 is greater than that of solution B2; Step S3: placing the mixed solution A obtained in step S2 in a constant temperature reactor and setting the temperature to change in stages, the whole change process includes a heating stage, a constant temperature stage and a cooling stage, while the temperature of the mixed solution A changes in stages, adding solution B1 and solution B2 to the mixed solution A in stages to react, collecting the product by centrifugation after the reaction is completed, vacuum drying the product and grinding it to obtain a NiFe2O4 / ZIF-8 precursor; Step S4: The NiFe2O4 / ZIF-8 precursor obtained in step S3 is pyrolyzed at 900-1000° C. under the protection of a nitrogen, hydrogen and helium mixed gas to obtain a NiFe2O4 / ZIF-8 electrocatalyst.

2. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: In step S1, the feed ratio of ferric acetylacetonate, nickel acetylacetonate, 1,2-hexadecanediol, oleylamine, oleic acid and dibenzene ether is 2mmol:1mmol:6~10mmol:4~8mmol:4~8mmol:20~60mL.

3. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: The reaction conditions of the heating reaction process in step S1 are an oxygen-free N2 environment, and the heating reaction process is a programmed temperature increase, specifically, first heating to 100-120°C and maintaining for 1-2 hours, then heating to 200-220°C and maintaining for 1-3 hours, and then continuing to heat to 290-300°C and maintaining for 1-2 hours.

4. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: In step S1, the centrifugal condition is 9000-10000 rpm, the centrifugal time is 3-10 min, the washing condition is n-hexane dispersion followed by ethanol precipitation, and the freeze-drying time is 24-60 h; in step S3, the centrifugal condition is 8000-9000 rpm, the centrifugal time is 3-8 min, the washing solvent is ethanol, the vacuum drying temperature is 50-70° C., and the vacuum drying time is 10-15 h.

5. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: In step S2, the feed mass ratio of Zn(NO3)2·6H2O, NiFe2O4 nanoparticles and copolymer PNIPAM-PAA is 300~400:1:1~3; the feed mass ratio of Zn(NO3)2·6H2O and dimethylimidazole is 1:0.5~2, and the concentration ratio of solution B1 and solution B2 is 2:

1.

6. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: The specific process of the heating stage in step S3 is heating from 30°C to 70°C, and the heating time is 30 minutes; the specific process of the constant temperature stage is maintaining at 70°C for 30 minutes; the specific process of the cooling stage is cooling from 70°C to 30°C, and the cooling time is 30 minutes.

7. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: In step S3, solution B1 is added dropwise to the mixed solution A during the heating stage, and the duration of adding solution B1 is consistent with the duration of the heating stage; In the constant temperature stage, solution B2 is added dropwise to the mixed solution A, and the duration of adding solution B2 is consistent with the duration of the constant temperature stage.

8. The method for preparing a NiFe2O4 / ZIF-8 catalyst based on spatiotemporal gradient assembly according to claim 1, characterized in that: The specific process of pyrolysis in step S4 is to heat the mixture to 950°C at a heating rate of 5°C / min and maintain it for 2h under the protection of nitrogen, hydrogen and helium mixed gas, wherein the volume fraction of hydrogen is 10%, the volume fraction of helium is 1%~2%, and the balance is nitrogen.

9. Use of a NiFe2O4 / ZIF-8 catalyst prepared according to the method of any one of claims 1 to 8 in catalyzing oxygen reduction and oxygen evolution reactions, wherein the ORR performance of the NiFe2O4 / ZIF-8 catalyst in a 0.1M KOH solution is a half-wave potential of 0.88 V, and the OER performance in a 1M KOH solution is a half-wave potential of 0.88 V at 10 mA cm -2 The overpotential is 330mV.

10. Use of the NiFe2O4 / ZIF-8 catalyst prepared according to the method of any one of claims 1 to 8 in preparing a cathode of a zinc-air battery.